Reflection of Hydropolitical Actions of Upstream Tigris and Euphrates Countries on Islamic Republic of Iran\'s Security: Case study Gap Project in Turkey - Ahmad Rashidinejad; Morad kaviani rad; Mottaqi (تحقیقات کاربردی علوم جغرافیایی)
The position of the Tigris and Euphrates rivers is in the least compatible with national borders or with the political and strategic considerations of regional countries. The sources of the Tigris and Euphrates rivers are located in Turkey, and Turkish authorities believe they own the resources. A project called "Gap" or "Anatolian" in the framework of the construction of more than 22 dams and 19 hydroelectric projects and development of the agricultural system in the Tigris and Euphrates watersheds has been on the Turkish governmentchr('39')s agenda by 2023, reflecting the security threat. The environmental and water security of the downstream countries (Iraq, Syria and Iran) have been demonstrated. The present study is based on the assumption of reflecting the Hydropolitic relations of the Tigris and Euphrates basin (based on Gap Project) with the viewpoint of continuing climate change and changing rainfall patterns and increasing water use in downstream countries using library resources. In the form of a threat to the security of the southwestern areas of Iran, it will intensify. The results showed that the consequences of the Hydropolitic approach of the Tigris and Euphrates countries, especially Turkey, besides threatening environmental security, affect other aspects of security in the economic, social and political spheres in the southwest of the country.